2003
DOI: 10.11130/jei.2003.18.4.817
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Small Firm Growth in the Greek Manufacturing Sector

Abstract: The aim of this paper is twofold; first, to identify the variables that mostly affect rapid sales growth in Greek manufacturing small and medium sized enterprises (SMEs); second, to examine the potential influence upon business growth and performance outcomes of those variables representing enterprise and financial management characteristics of the Greek SMEs. The study utilizes panel data of a random sample of 143 firms from the manufacturing SMEs sector in Greece. Regression analysis is used to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 23 publications
5
23
0
Order By: Relevance
“…Many studies have analyzed the effects of age or experience on firm growth (e.g., Audretsch and Lehman 2005;Oliveira and Fortunato 2004a, b;Voulgaris et al 2003;Fotopoulos and Louri 2004). These studies are closely related to Jovanovic's (1982) model, which found that Gibrat's law is not satisfied when firms are young and smaller than the MES.…”
Section: Econometric Methodologymentioning
confidence: 98%
See 1 more Smart Citation
“…Many studies have analyzed the effects of age or experience on firm growth (e.g., Audretsch and Lehman 2005;Oliveira and Fortunato 2004a, b;Voulgaris et al 2003;Fotopoulos and Louri 2004). These studies are closely related to Jovanovic's (1982) model, which found that Gibrat's law is not satisfied when firms are young and smaller than the MES.…”
Section: Econometric Methodologymentioning
confidence: 98%
“…Authors such as Voulgaris et al (2003) and Das (1995) recently used panel data to analyze the effect of firm size on firm growth.…”
Section: Econometric Methodologymentioning
confidence: 99%
“…According to Voulgaris et al (2003), successful growth of firms was related to entrepreneurial attributes. Moreover, the same researchers found that many entrepreneurs choose not to grow because of fear of loss of personal control over the firm, fear of having to go into debt or reluctance to pass the responsibility of running the business over to professional managers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, small enterprises still face many problems in their growth performance (Kirby& Kaiser 2003). These include low access to finance (Voulgaris et al 2003) and difficulties in getting loans from banks, which are due to their lack of collateral and adequate financial statements (Harner 2003), as well as poor managerial and business skills (Olawale and Garwe, 2010).According to Harner (2003), the high interest rates pose the most challenging obstacles in obtaining loans for small firms. Furthermore, as it is emphasized by Knowles and White (1995), no one should start a business in today's economy without a business plan.…”
Section: Introductionmentioning
confidence: 99%
“…They identified business management, financial conditions and owner-manager characteristics as being the most important factors to success. Voulgaris et al (2003) examined factors mostly affect rapid sales growth in Greek small and medium manufacturing Enterprises (SMEs). They believe that policies such as low cost financing, low tax burdens, incentives for investments in new technology, continuous personnel training, promotion of ecommerce and cooperation with foreign firms induce fast growth in Greek SMEs.…”
Section: Previous Related Literaturementioning
confidence: 99%